The Role of MSMEs In Reducing Unemployment Rate: Case Study in Langkat District - Hilma Harmen; Aprilda Yanti; Arisman Parhusip; Sienny; Amril (Outline Publisher, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in reducing the unemployment rate in Langkat Regency. MSMEs have long been considered a sector that is able to absorb a large number of workers, especially in areas with minimal large-scale industrial investment. This study uses a quantitative approach with a survey method of 100 MSME actors in 10 sub-districts. The variables studied include the number of MSMEs, government support, access to capital, and unemployment rates. Data were analyzed using multiple linear regression, validity tests, reliability tests, and classical assumption tests. The results of the study indicate that the number of MSMEs has a significant and negative effect on the unemployment rate, meaning that an increase in the number of MSMEs can reduce unemployment in Langkat Regency. Meanwhile, the variables of government support and access to capital do not have a significant effect. These findings indicate the need for strengthening more targeted policies in supporting MSMEs, either through financing, training, or regulations that facilitate the growth of small businesses. Thus, MSMEs have proven to have great potential as a strategic solution in overcoming unemployment at the local level.